Identification of dihydrogambogic acid as a matrix metalloproteinase 1 inhibitor by high-throughput screening - Li Y; Voorhees JJ; Fisher GJ (Dove Medical Press, 2017)
Yong Li, John J Voorhees, Gary J FisherDepartment of Dermatology, University of Michigan, Ann Arbor, MI, USAType I collagen (COL1) is the predominant structural protein in the skin. COL1 forms densely packed fibrils which are essential for maintaining skin mechanical properties and youthful appearance.1 The enzyme matrix metalloproteinase-1 (MMP1) cleaves COL1 fibrils at a single site.2 Once cleaved by MMP1, COL1 fibrils can be degraded by other proteases. MMP1 expression is elevated during natural aging and chronic sun exposure, ie, photoaging, leading to excessive degradation of COL1.3 This excessive degradation contributes to COL1 deficiency in the skin of the elderly. COL1 deficiency impairs skin structural integrity and appearance.Given the detrimental role of MMP1 in mediating age-associated fragmentation of COL1 fibrils, it would be beneficial to include MMP1 inhibitors in topical antiaging skin care products. Naturally existing substances that are safe for human use, such as botanical extracts, are often used in skin care products. We have utilized highthroughput screening (HTS) to identify naturally existing MMP1 inhibitors that could be used for cosmetic purposes.